Physiological and Molecular Mechanisms of Differential Sensitivity of Palmer Amaranth (Amaranthus palmeri) to Mesotrione at Varying Growth Temperatures - Godar, A. S.; Varanasi, V. K.; Nakka, S.; Vara Prasad, P.V.; Thompson, Curtis R.; Jugulam, Mithila (My University, 2015)
Herbicide efficacy is known to be influenced by temperature, however, underlying mechanism(s) are poorly understood. A marked alteration in mesotrione [a 4-hydroxyphenylpyruvate dioxygenase (HPPD) inhibitor] efficacy on Palmer amaranth (Amaranthus palmeri S. Watson) was observed when grown under low- (LT, 25/15 degrees C, day/night temperatures) and high (HT, 40/30 degrees C) temperature compared to optimum (OT, 32.5/22.5 degrees C) temperature. Based on plant height, injury, and mortality, Palmer amaranth was more sensitive to mesotrione at LT and less sensitive at HT compared to OT (ED50 for mortality; 18.5, 52.3, and 63.7 g ai ha(-1), respectively). Similar responses were observed for leaf chlorophyll index and photochemical efficiency of PSII (F-v/F-m). Furthermore, mesotrione translocation and metabolism, and HPPD expression data strongly supported such variation. Relatively more mesotrione was translocated to meristematic regions at LT or OT than at HT. Based on T-50 values (time required to metabolize 50% of the C-14 mesotrione), plants at HT metabolized mesotrione faster than those at LT or OT (T-50; 13, 21, and 16.5 h, respectively). The relative HPPD: CPS (carbamoyl phosphate synthetase) or HPPD:beta-tubulin expression in mesotrione-treated plants increased over time in all temperature regimes; however, at 48 HAT, the HPPD:beta-tubulin expression was exceedingly higher at HT compared to LT or OT (18.4-, 3.1-, and 3.5-fold relative to untreated plants, respectively). These findings together with an integrated understanding of other interacting key environmental factors will have important implications for a predictable approach for effective weed management.
Citation: Godar, A. S., Varanasi, V. K., Nakka, S., Prasad, P. V. V., Thompson, C. R., & Mithila, J. (2015). Physiological and Molecular Mechanisms of Differential Sensitivity of Palmer Amaranth (Amaranthus palmeri) to Mesotrione at Varying Growth Temperatures. Plos One, 10(5), 17. doi:10.1371/journal.pone.0126731
Keywords: Soybeans Glycine-Max; Relative-Humidity; Herbicide Resistance; Gene-Expression; Rapid Evolution; Lolium-Rigidum